2020
DOI: 10.3390/nu12092582
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Demographic Characteristics and Food Choice Motives with the Consumption of Functional Foods in Emerging Adults

Abstract: The functional food market is one of the fastest growing segments of the global food industry. The aims of this study were to understand the association of demographic characteristics and food choice motives (FCMs) with (a) attitudes toward functional foods and (b) consumption of functional foods in Australian emerging adults. Data were collected through a paper-based and online questionnaire completed by 370 young adults aged between 17 and 29 years. A binomial logistic regression was used to determine the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 65 publications
(147 reference statements)
0
20
0
1
Order By: Relevance
“…Regarding reasons to buy, the authors of [40] found that price, sensory appeal, convenience, and health were strong motives contributing to food choices. These authors also reported that young adults who value the food choice motives of weight control and natural content are likely to have a very positive attitude towards functional food.…”
Section: Figurementioning
confidence: 99%
“…Regarding reasons to buy, the authors of [40] found that price, sensory appeal, convenience, and health were strong motives contributing to food choices. These authors also reported that young adults who value the food choice motives of weight control and natural content are likely to have a very positive attitude towards functional food.…”
Section: Figurementioning
confidence: 99%
“…Our research also aimed to assess the differences between consumer groups in terms of their perception of health impacts. Research has highlighted the relationship between consumer characteristics (gender, age, level of education) and the assessment of functional foods [55][56][57]. Several studies have concluded that women are more open to functional foods than men, and those with a higher education level and the older age group have a completely different attitude towards the perception of functional foods than those with a lower education level or those who are younger in age [56][57][58][59][60][61].…”
Section: Aim Of Researchmentioning
confidence: 99%
“…Young university students who belong to the young adults segment represent the population core in transition to the adult stage marked by the independence of their homes and the responsibility for shopping [66,70]. Moreover, they are especially willing to buy functional products [64,65]. Young adults, will do so not only for themselves and/or their children, but perhaps for their parents as well [67,69].…”
Section: Discussionmentioning
confidence: 99%
“…As far as the dimensioning of specific populations is concerned, research on the university population is of particular interest. This segment of the population is known as young adults [64]. Young adults are especially willing to buy foods that reduce the risk of disease or help them to be healthier [65].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation